2010
DOI: 10.1589/jpts.22.209
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Effects of Manual Breathing Assist Technique (MBAT) and Shaking in Central Nervous System Disease Sufferers

Abstract: Abstract. [Purpose] This research was carried out to evaluate the effects of Manual Breathing Assist Technique (MBAT) and shaking on the ventilation of central nervous system (CNS) disease patients.[Subjects and Methods] The subjects were thirteen healthy individuals (normal group) and twenty-one CNS diseases sufferers without upper airway obstruction (subject group). We evaluates of Tidal Volume (TV), Peak Expiratory Flow Rate (PEFR) and Expiratory Time (Te) under rest respiration, MBAT, and shaking conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Expiratory abdominal compression (EAC) is a breathing assistance technique performed by abdominal compression during expiration. In previous studies, EAC for patients with neuromuscular disease or bronchial asthma was performed with powerful compression on the abdomen like the Heimlich maneuver 4 , 5 , 6 , 7 ) . In contact, EAC for patients with spinal cord injuries, patients after thoracoabdominal surgery, or patients with prolonged mechanical ventilation was performed gently 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Expiratory abdominal compression (EAC) is a breathing assistance technique performed by abdominal compression during expiration. In previous studies, EAC for patients with neuromuscular disease or bronchial asthma was performed with powerful compression on the abdomen like the Heimlich maneuver 4 , 5 , 6 , 7 ) . In contact, EAC for patients with spinal cord injuries, patients after thoracoabdominal surgery, or patients with prolonged mechanical ventilation was performed gently 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, respiratory assistance procedures, including rib springing technique, have been shown to be effective in improving ventilation [1][2][3][4][5][6] . The results obtained in our study further confirms that both techniques are effective in improving ventilation volume, in line with previous studies, by inducing deep inhalation through the elastic force of the chest, which is generated by the assisting chest wall movement during exhalation and alleviating the assistance during inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory assistance is a procedure performed by placing the palm on the patient's chest, and applying pressure in the direction of physiological motion during exhalation, and releasing the pressure during the following inhalation. The results of the procedure include increased tidal volume, improved ventilation, mitigated breathing difficulty, improved rib cage flexibility, and others [1][2][3][4][5][6] . It is one of the most popular and distinctive procedures for respiratory physical therapy in Japan 5) .…”
Section: Introductionmentioning
confidence: 99%
“…EAC is performed using compression on the abdomen above the navel. Several studies reported application of EAC to patients with respiratory failure such as amyotrophic lateral sclerosis, spinal cord injuries, central nervous system disease, and muscular dystrophy 4 , 5 , 6 , 7 , 8 ) . Another reported EAC with powerful compression, like the Heimlich maneuver, synchronized with coughing for the purpose of assisting coughing 9 ) .…”
Section: Introductionmentioning
confidence: 99%